2022
DOI: 10.3390/ijms232314677
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Dysregulation of Inflammation-Related Genes in Leukocytes of Patients with Gestational Diabetes Mellitus (GDM) during and after Pregnancy: Identifying Potential Biomarkers Relevant to Glycemic Abnormality

Abstract: Although the immune system has been implicated in the pathophysiology of gestational diabetes mellitus (GDM) and postpartum abnormal glucose tolerance (AGT), little is known about the transcriptional response of inflammation-related genes linked to metabolic phenotypes of GDM women during and after pregnancy, which may be potential diagnostic classifiers for GDM and biomarkers for predicting AGT. To address these questions, gene expression of IL6, IL8, IL10, IL13, IL18, TNFA, and the nuclear factor κB (NFκB)/R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 78 publications
1
0
0
Order By: Relevance
“…Subsequent gene ontology term and pathway analyses using these mRNAs suggested that immune and inflammatory functional categories were important for the pathogenesis of GDM. This is consistent with a recent study demonstrating higher expression of inflammation-related genes in blood cells from women with GDM compared to women with normal glucose tolerance [ 81 ] and earlier studies suggesting an important role for inflammation in GDM [ 82 ].…”
Section: Genetics Of Gdmsupporting
confidence: 93%
“…Subsequent gene ontology term and pathway analyses using these mRNAs suggested that immune and inflammatory functional categories were important for the pathogenesis of GDM. This is consistent with a recent study demonstrating higher expression of inflammation-related genes in blood cells from women with GDM compared to women with normal glucose tolerance [ 81 ] and earlier studies suggesting an important role for inflammation in GDM [ 82 ].…”
Section: Genetics Of Gdmsupporting
confidence: 93%